Assessment of the relationship between maxillary sinus floor and maxillary posterior teeth root apices using spiral CT scan - Hussein, Zainab Abdulhasan; Al-Nakib, Lamia H (Journal of Baghdad College of Dentistry, 2013)
Background: The purpose of this study is to investigate the relationship between the roots of the maxillary posterior teeth and the maxillary sinus using spiral computed tomography, and measured the distances between the roots of the maxillary posterior teeth and the sinus floor. Materials and Methods: The sample of the present study was a total of 120 Iraqi subject (60 males & 60 females) aged (20-60) years old, who admitted to spiral Computed Tomography scan unit in AL-Zahraa hospital in AL-Kut city to have Computed Tomography scan of the brain and paranasal sinuses who had complaints of headaches or with suspicion of sinusitis but without pathological findings in maxillary sinuses. From November 2012 to April 2013, CT sagittal reconstructed images were used in this study, Images were classified according to the relation between the root apices and the maxillary sinus floor into type1: Root apices below the sinus floor, type 2: Root apices in cosines floor. Vertical distance were measured between the deepest point of the maxillary sinus floor and the root apices of the maxillary first and second premolars and first, second molar contact with the sinus floor) and type 3: Root apices penetrate or inside the r using built-in measurement tools. Means, standard deviations and minimum and maximum values were calculated for all right and left premolars and molars. t-tests were used to compare measurements between left and right sides and between female and male patients. Results: The distance between sinus floor and root apex was longest for the first premolar palatal root apex and shortest for the second molar mesoibuccal root apex for both right and left sides. No statistically significant differences were found between the right and left side measurements or between females and males patients. Conclusion: There was no significant difference in vertical relation of maxillary posterior teeth to floor of maxillary sinus between male and female and between right and left side. The mesiobuccal root of the maxillary 2nd molar was closest to the maxillary sinus floor and palatal root of 1st premolar was farthest to the sinus floor.